Modeling of hysteretic shear-flexure hinges for dynamic analysis of 2-D reinforced concrete beams and columns - Enclona, Robin James E.
Ozcebe's Hysteresis Rule and Xu-Zhang's Hysteretic Shear and Flexure equations are implemented for reinforced concrete (RC) frame analys is without shear walls under seismic loading. The modeling of the strength degradation of the RC element is relevant for seismic design or analys is. Current conventional software however are not able to capture the strength degradation of the RC element (Deierlein, et al., 2010) and therefore insufficient for seismic design and analysis. A Plastic Hinge Model is chosen for nonlinear analysis because of its flexibility and simplicity compared to other models that simulate nonlinear behavior. The Xu-Zhang Hysteretic Shear and Flexure equations do not exhibit any interaction when computing their corresponding forces. Interaction happens at the derivation of the primary curve parameters that are needed for the hinge model. A Plastic Hinge Model is programmed for implementation on an open source program named wxAero to simulate the effect of both hinges run simultaneously. The contribution of shear deformation to the total displacement is observed in the pinching behavior of the total hysteretic curve allowing it to reach the peak of the cycle. The contribution of flexure however, for flexure-dominated columns, is the reloading stiffness below the crack load that displays insignificant pinching behavior. When combined together the total contribution of the behavior of both shear and flexure yields an agreeable result to the experimental data.